THE INFLUENCE OF TRAINING, DISCIPLINE AND FACILITIES ON SATISFACTION AND ITS IMPACT ON THE PERFORMANCE OF STATE CIVIL APPARATUS IN THE REGIONAL SECRETARIAT OF MEDAN CITY - Panjaitan, Ferry; Sianipar, Lasma Lenida; Gultom, Priska (SULTANIST: Jurnal Manajemen dan Keuangan, 2023)
This research was conducted in the Medan City regional secretariat environment, where this research is quantitative descriptive research, which explains training, discipline, facilities, satisfaction, and performance. This research also tests the relationship between these variables directly and indirectly. The population in this study were all employees at the Medan City Regional Secretariat, totaling 205 people spread across 12 work units. The total research sample was 68 people, determined using the Slovin (2001) formula with an error rate in sampling of 10%. The list of questions in this research was first tested for validity and reliability, the data was processed with the help of the SPSS version 25 program. The results of this research show that Training, discipline, and satisfaction have a positive and significant influence on performance, while Facilities do not have a significant influence on the performance of the City Regional Secretariat ASN Medan. Training, discipline, and facilities partially do not have a significant effect on the job satisfaction of ASN of the Medan City Regional Secretariat. For testing the path analysis, it shows that the training, discipline, and facilities variables both have no significant effect on performance through job satisfaction of ASN of the Medan City Regional Secretariat.